2015
DOI: 10.1002/ejoc.201500822
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Component Synthesis of 7‐Hydroxy‐7‐polyfluoroalkylhexahydroimidazo[1,2‐a]­pyridin‐5(1H)‐ones

Abstract: A new straightforward three‐component approach to 7‐hydroxy‐7‐(polyfluoroalkyl)hexahydroimidazo[1,2‐a]pyridin‐5(1H)‐ones with high diastereoselectivity and regiospecificity was developed starting from commercially available 3‐oxo esters, methyl ketones, and 1,2‐ethanediamines. The scope of this cyclization and its plausible mechanism are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…We recently developed a straightforward approach to 7‐hydroxy‐7‐polyfluoroalkylhexahydroimidazo[1,2‐ a ]pyridin‐5‐ones 1 based on a three‐component cyclization of readily available fluorinated 3‐oxo esters, aldehydes, and 1,2‐diamines (Scheme ). We found that when heterocycles 1a – 1i are heated under acidic conditions, they undergo both a dehydration at the C‐6–C‐7 bond and a ring‐opening of imidazolidine moiety at the C‐8a–N‐1 bond to form 1‐(2‐aminoethyl)pyridones 2 – 4 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently developed a straightforward approach to 7‐hydroxy‐7‐polyfluoroalkylhexahydroimidazo[1,2‐ a ]pyridin‐5‐ones 1 based on a three‐component cyclization of readily available fluorinated 3‐oxo esters, aldehydes, and 1,2‐diamines (Scheme ). We found that when heterocycles 1a – 1i are heated under acidic conditions, they undergo both a dehydration at the C‐6–C‐7 bond and a ring‐opening of imidazolidine moiety at the C‐8a–N‐1 bond to form 1‐(2‐aminoethyl)pyridones 2 – 4 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Column chromatography was carried out on Merck silica gel 60 (0.063–0.200 mm). Hexahydroimidazo[1,2‐ a ]pyridines 1a – 1i were obtained according to literature procedures . Glacial acetic acid and p ‐toluenesulfonic acid monohydrate were commercially sourced (purchased from Alfa Aesar).…”
Section: Methodsmentioning
confidence: 99%
“…Multicomponent synthesis is the most modern, simple and low-cost way to create new molecules from available starting reagents. Over the past 7 years, our group has been developing a new multicomponent approach that makes it possible to obtain various fluorine-containing heterocyclic compounds from commercially available polyfluoroalkyl-3-oxo esters, methyl ketones, and nucleophiles [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%